Development of Goal Sensor in Futsal Goal Using Pattern Detection - David Susilo Budi; Amir Supriadi (Jurnal Pendidikan Jasmani (JPJ), 2021)
Development of Goal Sensor Tools in Futsal Sports is a tool in matches and training to detect goals in futsal games. This tool can help teams, coaches and referees in detecting goals in matches and training. This tool was made with the aim of assisting the coach in applying the game system to defend and attack in order to get goals and so as not to concede. This tool serves to detect goals without any doubt in goal decision making.This study aims to develop a goal sensor to assist in matches and training. The population in this study were 30 athletes from the Joint Club FS and Tibor FC as well as 6 experts in each field. The form of the tool that has been made in advance is validated by 3 experts, namely 1 sports expert from the University who has a sports education background, 1 futsal coach expert and 1 electronics expert. The small group test involved 10 athletes and 3 experts, then the results were validated with an average value of the third validity of 77%. The results of the large group trial involved 20 people and 6 experts, then the results were validated with an average value of the sixth validity of 84%. Based on the results of validation by experts, it can be concluded that the development of a goal sensor in the futsal goal using 2020 pattern detection is valid and can be used. However, this tool cannot be disseminated because there are still many shortcomings in this tool.